Application of Adsorption Chromatography in the Papain Processing - He, Yuhai; Syed Mohd Saufi, Tuan Chik; Chong, Fui Chin (Global Science and Technology Forum, 2014)
A direct recovery of papain enzyme from unclarified Carica papaya juice was developed successfully using a reversed phase expanded bed adsorption chromatography (RP-EBAC). The dynamic binding capacity for the RP-EBAC at 10% breakthrough of 810.52 μg papain/g adsorbent was achieved at a linear flow velocity of 936 cm/h, bed expansion of two and feedstock viscosity of 2.68 mPa· s. Two-step elution was employed to enhance the purity of papain in RP-EBAC which gives high papain purity of 74.98% and high purification factor of 7.04. This work shows a great potential of using RP-EBAC with elution optimization step to purify papain from unclarified Carica papaya juice.